Development of multisubstituted hydroxyapatite nanopowders as biomedical materials for bone tissue engineering applications. Issue 6 (12th April 2017) - Baba Ismail, Yanny M.; Wimpenny, Ian; Bretcanu, Oana; Dalgarno, Kenneth; El Haj, Alicia J.
Abstract: Ionic substitutions have been proposed as a tool to control the functional behavior of synthetic hydroxyapatite (HA), particularly for Bone Tissue Engineering applications. The effect of simultaneous substitution of different levels of carbonate (CO3 ) and silicon (Si) ions in the HA lattice was investigated. Furthermore, human bone marrow‐derived mesenchymal stem cells (hMSCs) were cultured on multi‐substituted HA (SiCHA) to determine if biomimetic chemical compositions were osteoconductive. Of the four different compositions investigates, SiCHA‐1 (0.58 wt % Si) and SiCHA‐2 (0.45 wt % Si) showed missing bands for CO3 and Si using FTIR analysis, indicating competition for occupation of the phosphate site in the HA lattice; 500°C was considered the most favorable calcination temperature as: (i) the powders produced possessed a similar amount of CO3 (2–8 wt %) and Si (<1.0 wt %) as present in native bone; and (ii) there was a minimal loss of CO3 and Si from the HA structure to the surroundings during calcination. Higher Si content in SiCHA‐1 led to lower cell viability and at most hindered proliferation, but no toxicity effect occurred. While, lower Si content in SiCHA‐2 showed the highest ALP/DNA ratio after 21 days culture with hMSCs, indicating that the powder may stimulate osteogenic behavior to a greater extent than other powders. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1775–1785, 2017.